Correction to: The Kendrick modelling platform: language abstractions and tools for epidemiology - Mai Anh BUI T; Nick Papoulias; Serge Stinckwich; Mikal Ziane; Benjamin Roche (BMC Bioinformatics, 2019)
Following publication of the original article [1], the author noticed that the following lines were missing from the published article. The original article has been corrected.